Analisis Kelayakan Usaha Pembenihan Ikan Nila (Oreochromis niloticus) (Studi Kasus: Pusat Pelatihan Mandiri Kelautan dan Perikanan Mina Mandiri Muara Enim) - Triayu Rahmadiah; Muhammad Subhan Hamk; donny prariska (Clarias : Jurnal Perikanan Air Tawar, 2023)
The purpose of this study was to analyze the feasibility of tilapia seed production. Research location in Independent Training Center of Marine and Fisheries Mina Mandiri Muara Enim. The method used in this research is decriptive method. Data analysis methods are cost structure analysis, total production costs, total income, benefit analysis, revenue cost ratio (R/C ratio). From the results of data analysis has total income of Rp 150.000.000,-/month with a benefit cost of Rp 55.236.453,-/month, R/C ratio 1.58/ The results of the feasibility show that tilapia seed production in P2MKP Mina Mandiri Muara Enim is said to be feasible to be developed